Analysis of Waiting Times for Compound and Non-Compound Prescription Services At Al-Masoem Pharmacy in Cibiru, Bandung City - Shofwan, Adnan A.A.; Pitaloka, Dian A.E; Pradana, Eky S. (Pharmacology and Clinical Pharmacy Research, 2024)
Prescription services at Al Masoem Pharmacy, Cibiru should consider waiting time as one of the indicators for service provision to enhance service quality and ensure patient satisfaction. The aim of this research is to analyze the waiting time for prescription services at Al Masoem Pharmacy, Cibiru and assess compliance with the Minimum Service Standards for Pharmacies outlined in Minister of Health Regulation Number 73 of 2016. Observations of waiting times for prescription services at Al Masoem Pharmacy, Cibiru, located in Bandung Regency, were conducted over a period of 14 working days in February 2024, involving 365 prescriptions. This study utilized an observational method during the specified 14-day working period in February 2024, covering 365 prescriptions. The research findings indicate that both prepared and unprepared prescription services align with the time range specified in Ministerial Regulation No. 73 of 2016, which is 15-30 minutes. Based on observational data, the average waiting time for 44 compound prescriptions was 14 minutes and 18 seconds, while the average waiting time for 321 non-compound prescriptions was 7 minutes and 10 seconds.